Rita Wong’s monkeypuzzle and the Poetics of Social Justice - Kim, Christine (Studies in Canadian Literature, 2007)
Rita Wong’s poetry collection monkeypuzzle (1998) explores questions of gender, sexuality, race, labour, and globalization in relation to public culture. The poems address the complicated position their Chinese-Canadian female speaker occupies, moving between local, national, and global spaces to draw attention to the ways in which cultural, economic, and geographic positionings disrupt easy identifications with various communities. As both a site of aesthetic experimentation and ideological struggle, monkeypuzzle challenges the ways cultural representations of ethnicity and labour are mobilized by national and international spaces. The social theory of Himani Bannerji, Rinaldo Walcott, and Rey Chow offers insight into how Wong’s text resists the exploitative logic of capitalism through recourse to a postcolonial poetics, moving towards what Diana Brydon calls a politics of accountability.